Taxation Optimization Strategis In Indonesia To Increase National Revenue - Karona Cahya Susena; Nenden Restu Hidayah; Andika Cahya (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
Tax revenue plays a crucial role in financing national development and maintaining fiscal stability. However, tax collection in Indonesia has yet to reach its optimal potential. To increase national revenue, tax optimization strategis are needed, including improving tax compliance, reforming the tax system, and enhancing public tax literacy. Additionally, strengthening the tax base, monitoring tax avoidance, and utilizing information technology are vital factors in achieving this goal. Incentives for strategic economic secors and international collaboration to address cross-border tax avoidance can also boost national revenue. By implementing these strategies, Indonesia is expeced to optimize its tax potential and support sustainable national development.